Upaya Peningkatan Produksi Keripik Talas Melalui Penerapan Mesin Perajang Di Desa Balesari - Mulyaningsih, Nani; Choirul, Choirul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The process of processing taro into chips in Balesari Village, Magelang Regency has so far still carried out manually with simple tools and small capacity, so the results achieved still not quite to meet expectations. This purpose of this dedication is to make a taro chopper machine that can help workers process taro into chips quickly. The methods are a site survey, making taro chopper machine, handover of equipment to partners, training in operation and maintenance of the machine. The object is the craftsman of taro chips "Ibu Anik", Balesari Village, Magelang Regency. Tools and materials used are iron, plates, chopper blades, welding machines, lathes, saws pulleys, belts, paints, and electric motors. The results of dedication show that after the existence of taro chopper machines, it is able to increase partner production by 9x, faster.